Determining employee engagement and its influence on employee performance at holding state-owned enterprises insurance and guarantees Riau Islands region - Antony Sentoso; Evi Silvana Muchsinati (Jurnal Manajemen dan Pemasaran Jasa, 2024)
This study examines factors that determine employee engagement and its influence on employee performance. Furthermore, the independent variables consist of work environment, leadership, training & career development, compensation, team & co-worker relationships, workplace welfare, and organizational policies. The mediating variable in this study is employee engagement. Employee performance is the dependent variable in the implementation of this research. This research processes from primary data obtained from distributing questionnaires to all employees of the Insurance & Guarantee BUMN Holding in the Riau Islands region as many as 114 respondents are the population as well as the sample in this study using a total sampling method. This research utilizes the help of the Smart PLS data processing application. Data Analyzed from making SEM model, Validity and reliability test, and SEM Analysis Research showed that the work environment, leadership, training & career development, compensation, team & co-worker relations, workplace welfare, and organizational policies positively and significantly influence employee engagement and by mediating employee engagement show a significant effect on employee performance. The welfare of the workplace shows no significant results on employee engagement and no significant on employee performance with a mediating variable, namely employee engagement.